2006
DOI: 10.1002/bsl.706
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the M‐FAST: psychometric properties and utility to detect diagnostic specific malingering

Abstract: This study examined the ability of the M-FAST to differentiate a group of undergraduate students simulating one of four DSM-IV diagnoses (n = 190; schizophrenia, major depressive disorder, bipolar disorder, and posttraumatic stress disorder) and a clinical comparison sample drawn from previous M-FAST studies comprising individuals with the same diagnosis (n = 142). Across all diagnostic conditions, the simulators obtained higher M-FAST total scores than the clinical comparisons, and the rare combinations scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
(58 reference statements)
2
15
0
Order By: Relevance
“…The MMPI-2 has been found to better discriminate between genuine and feigning groups in simulation designs (Eakin et al, 2006;Lange et al, 2010); therefore, it is the preferred instrument. Examiners who use the PAI might consider supplementing it with a feigning-specific screener such as the Miller Forensic Assessment of Symptoms Test (M-FAST; Miller, 2001;Guy, Kwartner, & Miller, 2006) or the Structured Inventory of Malingered Symptomatology (SIMS; Widows & Smith, 2005). If you use the SIMS, be sure to use the higher cutoff score recommended in research by Wisdom, Challahan, and Shaw (2010).…”
Section: Screening and Assessment Of Exaggeration And Feigningmentioning
confidence: 99%
“…The MMPI-2 has been found to better discriminate between genuine and feigning groups in simulation designs (Eakin et al, 2006;Lange et al, 2010); therefore, it is the preferred instrument. Examiners who use the PAI might consider supplementing it with a feigning-specific screener such as the Miller Forensic Assessment of Symptoms Test (M-FAST; Miller, 2001;Guy, Kwartner, & Miller, 2006) or the Structured Inventory of Malingered Symptomatology (SIMS; Widows & Smith, 2005). If you use the SIMS, be sure to use the higher cutoff score recommended in research by Wisdom, Challahan, and Shaw (2010).…”
Section: Screening and Assessment Of Exaggeration And Feigningmentioning
confidence: 99%
“…Guriel-Tennant and Fremouw (2006) found that trauma history did not aid PTSD simulation, and in contrast to the earlier study, coaching decreased detection rates from 0.84 to 0.52. In the only study that examined discrimination of feigners from valid PTSD patients (noncompensation context, passed SIRS and MMPI-2 validity indicators), the M-FAST's standard cutoff score of six generated a sensitivity of 0.63 and specificity of 0.85 separating student simulators (Guy et al 2006).…”
Section: Screening Measuresmentioning
confidence: 99%
“…Guriel et al [19] showed M-FAST and TSI detected 90% of malingering to the PTSD and Guy et al [15] suggested that malingering people scored higher in the M-FAST than clinical participants (with Schizophrenia, major depression, bipolar and acute traumatic stress disorders). Jackson et al [16] indicated that the ≥6 score is a cutoff point for detecting malingering people in forensic assessment in prisons.…”
Section: Discussionmentioning
confidence: 99%
“…Strunk et al [14] showed that M-FAST correctly identified 78% of coached malingerers. Guriel et al [14] showed that M-FAST and Trauma Symptom Inventory (TSI) identified 90% cases of malingering of PTSD and Guy et al [15] showed that malingers got more score than clinical participants in M-FAST (with Schizophrenia, major depression, bipolar and acute traumatic stress disorders). Furthermore, Jackson and colleagues [16] indicated that the ≥6 score in forensic assessment is a cutoff point for detected malingers in prisons.…”
Section: Introductionmentioning
confidence: 99%